PENGARUH BEBAN PAJAK TANGGUHAN DAN AKTIVA PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PROPERTI DAN REAL ESTATE - cahya, wirantika; Maryama, siti (COMPETITIVE, 2021)
ABSTRACTWirantika Cahya, The Effects of Deferred Tax Expenses and Deferred Tax Assets on Earnings Management in Property and Real Estate Companies in the 2014-2018 period on the Indonesia Stock Exchange. Under the guidance of Mrs. Siti Maryama, .SE, .MM. This study aims to examine and analyze the effect of deferred tax expense and deferred tax assets simultaneously on earnings management in property and real estate companies in the 2014-2018 period on the Indonesia Stock Exchange. The values tested in this thesis use the SPSS (Statistical Package for Social Science) program version 25.0, using a logistic regression analysis tool. the results of this study found that the deferred tax expense affects earnings management because the p-value of 0.039 is smaller than 0.05 and has a beta with a negative coefficient of -0.082, while the deferred tax assets do not affect earnings management because the p-value of 0.053 is greater than 0.05 and has a beta with a positive coefficient of 0.452. Keywords: Deferred Tax Expenses, Deferred Tax Assets, and Profit Management